P507 What is the impact of infliximab metaoptimisation on surgical rates and need-to-change-therapy in real-world practice for severe inflammatory bowel disease?. (16th January 2018) - Lefebvre, T; Cormons, R; Faucheron, J -L; Baudrant, M; Bonaz, B; Mathieu, N
Abstract: Background: Current evidence-based recommendations do not recommend intensified Infliximab (IFX) regimens for patients with severe IBD. Nevertheless, retrospective single-centres analysis observed markedly lower early surgical rates. Our aim was to evaluate the efficacy of metaoptimised IFX (MIFX), i.e. combined intensified induction and maintenance regimen as compared with a standard IFX (SIFX) schedule historical cohort on 1 year surgical rates in severe hospitalised IBD patients. Methods: In this retrospective single centre study, two cohorts of patients with CD and UC who were hospitalised at our single teaching hospital for an acute severe flare were identified from 2014 to 2016 (MIFX cohort) and 2007 to 2014 (SIFX cohort) were identified. MIFX patients received a 10 mg/kg intravenous infusion of infliximab, then subsequent infusions, at Weeks 1 and 4, and every 4 weeks thereafter until end of follow-up. The patients were switched to a different TNF Inhibitor or another class of biological agent and/or surgery in case of IFX failure during the study. SIFX patients received a 5 mg/kg intravenous infusion of infliximab at Week 0, then subsequent infusions, at Weeks 2 and 6, and every 8 weeks thereafter until end of follow-up. Intensifying the IFX regimen, changing to a different TNF Inhibitor or another class of biological agent, and/or surgery was decided by the managing physician in case of IFX failure. Severe UC and CD were defined per clinical assessment with a Lichtiger Index > 12 for UC, a Harvey−Bradshaw Index (HBI) > 12 for CD and according to ECCO classification. Our primary endpoint was the 1-year surgery rates. Results: Ninety-five severe IBD patients (62 CD and 33 UC, 54 male and 41 female patients), with a median age 34 years (IQR, 25–52) were hospitalised, and IFX was initiated. They were included in the study with a median follow-up of 12 months: 28 MIFX patients and 67 SIFX. The clinical parameters, disease severity, biological data (CRP, FC, albumin), and previous treatments were comparable in both groups. A total of five of the 28 MIFX patients (18%) had a surgery, as compared with 21 of 67 SIFX (31%), patients with IFX metaoptimisation had almost a two-fold chance of being surgery-free at 1 year while not reaching statistical significance (OR: 0.48 [95% CI: 0.16–1.42], p = 0.18). MIFX patients had a three-fold chance to change their medical therapy at 1 year (25%) as compared with SIFX patients (9%) (OR: 3.39 [95% CI: 1.02–11.22], p = 0.05). The 1 year infections rate was greater in MIFX patients (OR: 2.21 [95% CI: 0.61–7.95], p = 0.11). Conclusions: Our study results suggest that patients with IFX metaoptimisation have a two-fold chance of being surgery-free at 1 year, and a three-fold chance to switch IFX at the one-year follow-up.